Quality Of Onion Sticks Substitute For Soybean Tempeh Flour - Rizkhi, Fiqi Mutiara; Holinesti, Rahmi (Jurnal Pendidikan Tata Boga dan Teknologi, 2022)
This study aims to analyze the effect of substitution of soy-based flour on the quality of onion sticks with the addition of 15%, 30% and 45% of soybean paste flour. This study was a pure experimental study with a randomized design method (CRD) consisting of 4 treatments and 3 repetitions. The object of this study was onion sticks with the addition of 15% 30% and 45% soybean tempeh flour. The independent variable in this study was soybean tempeh flour. The dependent variable of this research is the quality of the onion sticks produced including the shape, color, aroma, texture and taste. Data analysis was obtained from organoleptic tests involving 4 expert panelists, namely lecturers of Family Welfare Sciences, Padang State University. The data analysis technique used is analysis of variance (ANOVA) to analyze sensory test data. The data that has been obtained is then tabulated in tabular form and analyzed according to the test of each data. Then the data analysis is carried out if the data obtained by Fcount is greater than Ftable, then it is continued with Duncan's test. The results showed that the substitution of soybean tempe flour had an effect on the color, texture, taste and had no effect on the shape, aroma. Based on the results, the best research was found in the treatment (X1) 15% with categories of neat shape, golden yellow color, fragrant aroma, crumbly texture and savory taste, therefore for further research it is recommended to use soybean tempe flour with 15% substitution which produces good quality .